Small-scale Fishermen's Adaptation to Climate Change Impacts in Coastal Areas and Small Islands in Pangkep Regency - Kasri, Kasri; Hasani, M. Chasyim; Baso, Aris; Amiluddin, Amiluddin; Arief, Andi Adri (Torani Journal of Fisheries and Marine Science, 2024)
Climate change is a global challenge that has significant impacts on the fisheries sector. This phenomenon involves increasing global temperatures, changing weather patterns, rising sea levels, and increasing the frequency and intensity of natural disasters. Climate change not only threatens marine ecosystems but also affects the livelihoods of coastal communities, especially small-scale fishers who depend on fisheries resources for their survival. This study aims to analysis the economic adaptation of small-scale fishers in facing the impacts of climate change. The research was conducted from May to October 2024 in Pangkajene Islands Regency (Pangkep). This research used a descriptive qualitative approach with data collection through interviews, questionnaires, field observations, and literature studies. Respondents in this study were 50 fishermen who were selected purposively. Data analysis used with descriptive qualitative. The results show that climate change has a significant impact on fishing patterns and catches. The increase in sea temperature, high waves, and storms cause a decrease in productivity and increase the risk of damage to fishing gear. In facing these challenges, fishers apply economic adaptation strategies such as livelihood diversification, regulation of fishing period/time, improving fishing technology, changing fishing areas, and strengthening community cooperation. This research recommends strengthening the capacity of fishermen through training, access to microfinance, and development of disaster-resistant infrastructure. The results of this study are expected to serve as a basis for the government and stakeholders in formulating community-based adaptation policies to increase the resilience of small-scale fishing communities to the impacts of climate change.